ANALISIS REGRESI LINIER BERGANDA UNTUK MENGETAHUI PENGARUH CURAH HUJAN TERHADAP LUAS PANEN SERTA PRODUKSI PADI DAN JAGUNG DI JAWA TIMUR - Choirianisa, Agita; Abidin, Zainal; Yektiningsih, Endang (Berkala Ilmiah AGRIDEVINA, 2017)
The earth climate change is characterized by the earth temperatures increasing in polesand glaciers begins to melt so that the sea level increases and causes small islandsaround disappear. The seasonal change also happens in some countries in the world,such as the temperatures changing and the decreasing of rainfall intensity every yearincluding in Indonesia, especially in East Java Province. The influence of climate changein East Java gives an impact on crops production and productivity fluctuation on riceand maize cutivation whose existance is important for the sustainability of people’s dailylife. That climate condition can cause the unhealthy rice cultivation and not fullycorncobs. That climate change has an impact on one of the component itself, such asrainfall. This research was conducted to analyze the influence of rainfall on crops area,production, and productivity on rice and maize in East Java. Within 20 years, the riceand maize production increased. The trend analysis from rice and maize commodityshowed the increasing of crops area. The increasing of crops area was in line with theincreasing of production area. Beside that, there was an increasing of productivity whichcould support the existance of food security and the evenness fulfillment. Crops area hada significant influenceon the increasing of rice and maize production while rainfallaffects the significance of rice production.